The Impact of Rupiah Depreciation on the Indonesia Sharia Stock Index (ISSI): Implications for Sharia Investment Education (A Systematic Literature Review) - Noor Hafizah (STIT Darul Hijrah Martapura, 2025)
The depreciation of the Indonesian rupiah is a macroeconomic indicator that significantly influences capital market dynamics, particularly the Islamic capital market. Studies specifically examining the implications of rupiah depreciation on the Indonesia Sharia Stock Index (ISSI) remain limited, while most existing literature focuses on conventional stock markets. This study aims to identify, compare, and synthesize scientific findings regarding this relationship through a systematic literature review of 20 Indonesian-language scholarly articles published between 2015 and 2026. The findings indicate that rupiah depreciation generally exerts a negative impact on ISSI performance through two primary channels: the escalation of operational costs for companies dependent on imported raw materials and the increase in market uncertainty that encourages investors to shift toward safer instruments. However, these effects are not uniform, as export-oriented firms may potentially benefit from a weaker exchange rate. Other macroeconomic variables, such as inflation and interest rates, have also been shown to intensify the adverse effects of depreciation on the index. Furthermore, the Sharia-based screening mechanism provides ISSI with relative resilience compared to conventional indices amid external pressures. These findings underscore that the relationship between rupiah depreciation and ISSI is multidimensional, shaped by macroeconomic conditions, sectoral characteristics, issuers' business orientations, and investor sentiment.